Modern Mandarin Chinese Grammar - Ross, Claudia, Jing-heng Sheng Ma (Routledge, 2014)
This book is divided into two sections : 'structure' and 'situations and functions'. Part A 'Structures' is concise grammar of Mandarin Chinese organized in the familiar and traditional way, providing an overview of the Chinese writing system and describing the major features of Mandarin grammar. and part B 'Situations and functions' is organized in term of how to do things with language, and it is longer of the two sections.